A Preliminary Classification of Langkawi Island Streams Using Biotic Index Criteria - Siaw Yang, Yap (Malaysian Journal of Science, 2005)
The benthic macroinvertebrate community of ten running-water sites in Langkawi Island was investigated for its potential as a water quality indicator. The structure metrics measured were total taxa richness, Ephemeroptera-Plecoptera-Trichoptera (EPT) taxa richness, and the habitat-related Biological Monitoring Working Party (BMWP) scores. The clean water indicating assemblage or EPT taxa is considerably poor in richness (less than ten genera) and diversity while Atyidae dominates the freshwater shrimp assemblage. The midges (Chironomidae: Diptera) living in soft tubes are reasonably well represented at the lentic ecosystem. The BMWP scores based on twenty-eight families of macro-invertebrates vary widely from 5.8 to 91.5. Three sets of independent classification schemes suggest that the running-water sites belong to Classes IV and V of the Malaysian National Water Quality Standards, classifiable as degraded quality.